The Multidimensional Constructs of Organizational Justice and Organizational Commitment: Empirical Evidence From Public and Private Organizations in Indonesia - Fahrudin JS Pareke (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The multidimensional construct of organizational justice and organizational commitment has attracted longstanding attention and debate among managers, researchers and academicians. To achieve significant progress, studies in this area should be directed to investigate the two sides simultaneously, construct validity and substantive validity. So that the progress achieved can be balanced between the conceptualization and definition of the construct itself as well as the relationship and its effect on other constructs. Therefore, current study intents to test the validity dan reliability of four-factors of organizational justice (FFOJ) construct, and to test its effect on organizational commitment dimensions. The research respondents were 264 private employees and civil servants who studying in 3 graduate programs at University of Bengkulu, choosen using stratified random sampling. Two-hundred-and-fifty-seven respondents participated in the study. Data analysis used Factor Analysis, reliability test, and Hierarchical Regression Analysis (HRA). The conclusions of this study provide strong support for the FFOJ conceptualization. Of the 20 items questionnaire included in factor analysis, 19 items loaded in 4 dimensions, which is distributive justice (4 items), procedural justice (6 items), interactional justice (4 items), and informational justice (5 items). The reliability of all dimension are good, with Cronbach 'Alpha (α) score greater than 0.7. Almost all dimensions of FFOJ affect the dimensions of organizational commitment, except the interactional justice that has no effect on the affective commitment. Further investigation is highly recommended so that organizational justice measurement becomes more workable in explaining the phenomena of justice in the daily life of the organization. The empirical evidence also further emphasized the important role of organizational justice in order to foster, enhance, and maintain organizational commitment. Attempts to acquire employees with high organizational commitment will face serious obstacles when the employees still perceive there is no fairness in their organization.Keywords: afective commitment, continuance commitment, distributive justice, interactional justice, informational justice; procedural justice, normative commitment